Analysis of benthic macroinvertebrates biodiversity of Cunas river by means of environmental indicators, Junin-Peru - Custodio, María (2016)
The objective of the investigation was to analyze of benthic macroinvertebrates biodiversity of Cunas river by means of environmental indicators. Three sampling sectors were defined two contrasting periods. The anthropic pressures evaluation was carried out by means of DBO5 determination contributed by waste water. Water samples were collected for nitrate, phosphate and fecal coliform determination. The measured indicators in situ were: dissolved oxygen, dissolved total solids, conductivity, temperature, pH and turbidity. The benthic macroinvertebrate samples were collected using a Surber net with 250 µm wire netting opening. The anthropic pressure results on the benthic macroinvertebrates were: fish farming waste water DBO5 mean 7.70 mg/L, from livestock activity 869 mg/L and from urban activity 428.3 mg/L. The physicochemical and bacteriological indicator results showed significant differences for conductivity, temperature and dissolved total solids. Four phyla, seven classes, 12 orders and 26 benthic macroinvertebrate families were identified. It is concluded that waste water discharge from livestock and urban activities are significant anthropic pressures on benthic macroinvertebrate biodiversity. The water quality physicochemical and bacteriological indicators, determined according to sector and time sampling are in the ECA range for highland river water. The richness, abundance and benthic macroinvertebrate diversity, according to the sector and time sampling, presented significant differences.